Development of E-Comic Media to Improve Elementary School Students' Understanding of Discipline - Najibah, Fairuz; Abdullah, Kusmajid (Universitas Pendidikan Mandalika, 2025)
This study aims to develop e-comic media on the material of politeness norms to improve the understanding of discipline in elementary school students and to evaluate the feasibility and effectiveness of the e-comic media. This research uses the R&D (Research and Development) method with the ADDIE model and utilizes the Pre-Experimental Design One Group Pretest-Posttest Model. This study involved 24 fourth-grade students at SDN 1 Kaduagung Timur, Banten Province. Data collection was carried out in several ways, namely interviews, observations, questionnaires, and formative tests in the form of pre-test and post-test totaling 12 multiple-choice questions. The validation results obtained, such as media expert validation of 92.96%, material and question experts of 88.88% and 99.26%, and language experts of 91.39%. In addition, there are also the results of teacher response questionnaires, which get 97.14% and student response questionnaires reaching 92.34%, which shows that e-comic is well received as a learning medium. In terms of effectiveness, the Wilcoxon test revealed a significant difference between pretest and posttest results (p < 0.0001), also supported by the N-Gain value, which reached an average of 0.77 and was included in the high category. Therefore, the use of e-comic media for grade IV students has been proven effective and feasible to improve students' understanding of disciplinary values.